KURIKULUM BERBASIS KOMPETENSI PADA TVET: TINJAUAN SISTEMATIS TENTANG DESAIN, IMPLEMENTASI, DAN EVALUASI CBE/OBE - Nogi Handepi; Ambiyar; Hasan Maksum (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Changes in the world of work driven by digitalization, automation, and sustainability demands encourage Technical and Vocational Education and Training (TVET) institutions to adopt competency-based education (CBE) and outcome-based education (OBE). However, many reforms remain limited to curriculum documents, resulting in inconsistent graduate competency outcomes. This article presents a systematic literature review (SLR) based on the PRISMA 2020 guidelines to synthesize evidence from the last five years (2021–2026) regarding: (1) the characteristics of CBE/OBE design in TVET curricula, (2) determinants of implementation in practice, (3) evaluation approaches and the strength of evidence, and (4) the role of design–implementation–evaluation coherence in explaining outcome success. The literature search identified 516 records and resulted in 7 studies that met the inclusion criteria. Thematic synthesis indicates that strong curriculum design is characterized by measurable learning outcomes, explicit curriculum mapping, and the integration of digital and transversal competencies. Implementation is primarily influenced by instructor capacity, the availability of practical training facilities, and industry partnerships in work-based learning (WBL). In terms of evaluation, the weakest evidence lies in the reporting of assessment validity and reliability, assessor moderation, and the linkage between assessment outcomes, certification, and employability. This article proposes the CBE/OBE Coherence Framework, which emphasizes outcome–activity–assessment alignment audits, governance of industry partnerships, and data-driven feedback mechanisms as key strategies to bridge the gap in TVET curriculum reform